SOSIALISASI PEMBENIHAN IKAN NILA (Oreochromis Niloticus) DI DESA TIGA RAS KECAMATAN DOLOK PARDAMEAN KABUPATEN SIMALUNGUN - Mila Sianipar; Erwin Sapeai; Goldvri Hutabarat; Saut Silitonga; Ria Retno (Abdi Jurnal Publikasi, 2025)
Tilapia (Oreochromis niloticus) is one of the introduced fish species that is commonly cultivated in Indonesia. Tilapia cultivation in Indonesia has experienced a lot of improvement with the emergence of several breeding strains of tilapia. According to the KKP (2018), tilapia production in 2016 was 1,114,156 tons, in 2017 and 2018 tilapia production increased again with amounts of 1,265,201 tons and 1,169,144 tons respectively. The activity of growing seeds in fish is the beginning of activities in cultivation, most importantly because it can influence subsequent activities, namely nursery and rearing of broodstock. Overall hatchery includes brood care, brood sorting, breeding and larval rearing. Fish hatchery is one part of fish farming activities by mating broodstock to get young that are ready to be marketed. This article is the result of community service activities to provide material about tilapia fish hatcheries through outreach, so that people can carry out their own tilapia fish hatcheries.